PERAN GURU MADRASAH IBTIDAIYAH SWASTA KOTA PEKANBARU DALAM PROSES PEMBELAJARAN TEMATIK - Rahmadanni Pohan (STAI Nurul Falah Airmolek, 2017)
Teachers are professionals who are tasked with planning and implementing the learning process, assessing the results of learning, guiding and training, and conducting research and community service. There are a number of things that cause low public recognition of the teaching profession, namely the low level of professional competence,teacher mastery of the material and teaching methods are still below the standard. Thepurpose of this study was to determine the role of Madrasah Ibtidaiyah teachers in the thematic learning process and find out what are the factors that support the role of Madrasah Ibtidaiyah teachers in the thematic learning process.Qualitative descriptive research (naturalistic approach) from January to June2018 in Private Islamic Madrasah in Pekanbaru City. Data collection technique;nonparticipant observation, interviews, and documentation. Data analysis is reduction,display, and conclusion drawing / verification and source and technique triangulation.The results are indicated by the job description of the teacher in carrying out their duties as they should be able to increase the teacher's role in thematic learning,both in professional, social, personality, and pedagogic competence.